Arm symmetry in 11-13 years old front crawl swimmers - Silva, A.; Figueiredo, P.; Soares, S.; Vilas-Boas, J. P.; Fernandes, R. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to analyse the arm symmetry in age-group swimmers performing front crawl at very high intensity. Eighty trained swimmers of 11-13 years of age performed 25-m front crawl at 50-m pace. Two underwater cameras were used to assess the Index of Coordination (identifying each stroke phase) and the Symmetry Index. It was observed an asymmetry, which is in accordance with the results obtained for adult swimmers. It was also observed that only catch up mode was adopted by these young swimmers to achieve the swimming intensities corresponding to 50-m front crawl pace. Complementarily, the observed lower relative duration of the propulsive phases seems to be explained by the higher time spent during the entry/catch phase.